Early Pregnancy Blood Pressure Elevations and Risk for Maternal and Neonatal Morbidity. Issue 1 (July 2020) - Sutton, Elizabeth F.; Rogan, Sarah C.; Lopa, Samia; Sharbaugh, Danielle; Muldoon, Matthew F.; Catov, Janet M.
Abstract : OBJECTIVE: To investigate whether women with early pregnancy elevated blood pressure (BP) or stage 1 hypertension exhibit increased risk of preeclampsia and maternal or neonatal morbidity. METHODS: We conducted a clinical cohort study of 18, 162 women who delivered a singleton neonate from 2015 to 2018 and attended at least two prenatal appointments before 20 weeks of gestation. Data were collected within the Magee Obstetric Maternal and Infant database, an aggregate of prenatal and delivery health records. Early pregnancy BP was defined as average BP before 20 weeks of gestation, and women were classified with normal, elevated BP, stage 1 or 2 hypertension according to current guidelines. The primary outcome was preeclampsia. Secondary outcomes were severe maternal morbidity, placental abruption, gestational diabetes, and composite neonatal morbidity. RESULTS: Overall, 75.2% of the women were categorized with normal BP, 13.9% with elevated BP, 5.4% with stage 1 hypertension, and 5.5% with stage 2 hypertension. Risk of preeclampsia increased in a stepwise fashion with increasing BP category, adjusted for covariates (normal BP, 4.7%, referent; elevated BP, 7.3%, adjusted odds ratio [aOR] 1.29, 95% CI 1.07–1.56; stage 1, 12.3%, aOR 2.35, 95% CI 1.86–2.96), and stage 2, 30.2%, aOR 6.49, 95% CI 5.34–7.89). Results were similar among black and white women. Gestational diabetes was more prevalent among women with stage 1 (11.4%; aOR 1.50, 95% CI 1.18–1.91] and stage 2 hypertension (14.2%; aOR 1.65, 95% CI 1.30–2.10). Severe maternal morbidity and neonatal morbidity were increased only among women with stage 2 hypertension (aOR 2.99, 95% CI 2.26–3.99, and aOR 2.67, 95% CI 2.28–3.12, respectively). CONCLUSION: Women with elevated BP, and stage 1 and 2 hypertension in early pregnancy are at increased risk for preeclampsia. These findings emphasize the importance of applying the 2017 BP guidelines to reproductive-aged women. Strategies to incorporate these guidelines into obstetric care may also be warranted. Abstract : Entering pregnancy with elevated blood pressure or stage 1 or stage 2 hypertension classified by 2017 American College of Cardiology–American Heart Association guidelines is associated with an increased preeclampsia risk.